Teatro, memória, música e poesia na "Melhor Idade": relatos de uma vivência - LOPES, Neire Conceição Nunes (2021)
This present academic work has relates, that describing myself childhood memories how to meeting with grandfathers and grandmothers; of the mother, of the woman, of the chance that has brought me at the theatre and that made me choose this graduation course in theater and the implications of my choice showed me. Offered me see the relevance university extension activities between university and community and the contribution for Educational Training staff. On the Extension Project Theatre and Memory, Music and Poetry in the Best Age, I expanded may gaze about old age, I lived it in praxis teaching in the supervised stages I and II, knowing others realities, increasing discoveries that it will entangling my formation, when application, theory and the practice that bring-me knowledge about all those teaching/learning process, by choice knowledge field application and mine profile while theatre´s teacher.